(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background Many patients with coronavirus diseases (COVID-19) require intensive care unit (ICU) admission and mechanical breathing, with adverse results. Some research looked into hospital-acquired infections, particularly ventilator-associated pneumonia (VAP), as a cause of patient deterioration. Furthermore, the ICUs of COVID-19 centres must be sterilised and free of bacterial contaminations, as there are numerous links between the frequency of deaths and resistant bacterial co-infections. Respiratory viral-bacterial co-infection is linked to higher mortality and morbidity than either viral or bacterial infection alone. Objective Identification of incidence of resistant bacterial infections in the ICU of isolated COVID-19 patients. Material and Methods Fifty-five samples were taken from beds, tables, monitors, ventilators, baths, wash devices, and materials in the COVID-19 ICU. The samples were then cultivated, and bacteria resistance was assessed using Pheonix BD CPO. Results The samples were divided into sterilized (no bacterial growth) and non-sterilized (bacterial growth). We found that 32 samples (58.18%) were sterilized and the percentage of the most frequently isolated multi-drug resistance (MDR) gram-negative species was Acinatobacter. baumannii (26.08%), Pseudomonas. putida (13.04%), Klebsiella. pneumonia (8.69%), Achromobacter. species (8.69%), Pseudomonas. species (8.69%), Acinetobacter. baumannii/Calcoaceticus.complex (4.34%), Pseudomonas. pseudoalcaligenes (4.34%) respectively. Conclusion Based on the results of the trials, it can be stated that the prevalence of resistant bacteria is significant in the ICU of COVID-19, and this resistance may result in increased morbidity and death. Furthermore, the medications that affect this sort of resistant bacteria are restricted.